SAT0550 Familial Mediterranean Fever in the Greek Cypriot Population. Experience from Two Centres. (9th June 2015) - Psarelis, S.; MIna, E.; Nikiphorou, E.
Abstract : Background: Familial Mediterranean Fever (FMF) is an autoimmune inflammatory disease with autosomal recessive inheritance, characterized by recurrent serositis and episodes of fever. Previous genetic studies in Greek Cypriots have examined the frequency and the most common mutations observed in this population (1, 2). Objectives: To evaluate the clinical presentation of patients diagnosed with FMF and examine their genetic background and any association with clinical symptomatology. Methods: This was a retrospectively analysis of 34 patients with a known diagnosis of FMF according to the Tel–Hashomer criteria. All patients were genetically tested for the common mutations and divided into three groups: A homozygotes (6), B heterozygotes (20) and C complex heterozygotes (9). Binary logistic regression with the outcome being presence of a specific symptom or not was used to examine the effect of various linear or categorical predictors e.g. age at symptom onset or presence of a specific gene. Independent effects were examined using Odds Ratios. Results: Group A (homozygotes) consisted of the following genes: M694V, V726A, E-167-F479 (33%). The most common symptoms where abdominal pain (100%), fever (83%), joint pain (50%), chest pain (33%), pericarditis (16%). In group B (heterozygotes) the commonest mutation was V726A (35%), followed by E-167-F479 (30%), E148Q (20%) and M694V, R761H, K695R (5%). The most common symptoms where abdominal pain (65%), fever (60%), joint pain (30%), chest pain (33%). C group (complex heterozygotes) consisted of V726A- E-167-F479 and V726A-K695R (22%) mutations, and the V726A- R761H, V726A-M694V, V726A- E230K, V726A-M680I, M694V- M680I (11%). The most common symptoms in this group where fever (66%), abdominal pain (55%), joint pain (33%), chest pain (33%) pericarditis (11%). There were no statistically significant differences seen between the type of genetic composition and the timing of symptom-onset or clinical symptom presentation, possibly due to the small numbers used in the models. The odds of those less or equal to 15 years at symptom-onset for developing joint pain as one of the clinical manifestations were 0.85 times lower than those over 15 years, controlling for the three groups and gender in the models (p=0.04). There was no significant difference noted between other clinical manifestations and age, gender or genetic background. All patients were treated with colchine with good symptom-control. Only two patients (6%) (one heterozygote [V726A] the other homozygote [M694V]) where treated with additional tosilizumab and anakinra respectively due to incomplete symptom resolution, with a good outcome. Conclusions: This study showed that the V726A gene presence appears to be a common finding in all groups (Homozygotes, heterozygotes and complex heterozygous). Heterozygotes can present with similar clinical manifestations to homozygotes, with the commonest symptoms being abdominal pain and fever. Colchicine is a reasonable first line treatment for these patients. References: Vassos Neocleous, et al. Familial Mediterranean Fever Associated with MEFV Mutations in a Large Cohort of Cypriot Patients. Annals of Human Genetics 2014;00:1–8. Deltas K, et al. Familial Mediterranean Fever (FMF) Mutations Occur Frequently in the Greek Cypriot Population of Cyprus. Genetic Testing 2002;6(1). Disclosure of Interest: None declared